6 February 2023 Descriptive Analysis Of The Earthquake Storm In Turkey In Terms Of X (Twitter) - Demirhan, Tolga; Hacıoğlu, İlker (Fırat University, 2024)
On February 06, 2023, a major earthquake swarm occurred in Turkey. The earthquake was the main topic of social network posts after this event, which caused deep sadness across the country. Research has proven that social networks can be used as an important source for understanding public opinion in the face of real events. One of these networks, X (Twitter), is an important tool for sharing situations, opinions, requests for help and information, especially in natural disasters such as earthquakes. Although there are earthquake disaster analysis studies based on these posts, which are a rich source of data, more case studies are needed to verify the effectiveness of earthquake analysis methods. The aim of this study is to conduct descriptive analyses to determine the agenda, tendency and behavior of the public through tweets shared on network X during the earthquake storm. In this context, an application was developed using python language and libraries. With this application, in the first stage, a data set was created by retrieving 2,643,481 tweets containing the word "earthquake" in the X network between February 5-12, 2023. In the next stage, descriptive analyses were performed and results were obtained and these results were presented using data visualization tools. The results revealed the sharing behavior of users after a major disaster.

06 Şubat 2023 tarihinde Türkiye’de büyük bir deprem fırtınası gerçekleşmiştir. Tüm ülkede derin üzüntüye neden olan bu olay sonrasında sosyal ağ paylaşımlarının ana konusu deprem olmuştur. Araştırmalar, gerçek olaylar karşısında kamuoyu görüşlerinin anlaşılması için sosyal ağların önemli bir kaynak olarak kullanılabileceğini kanıtlamıştır. Bu ağlardan biri olan X (Twitter), özellikle deprem gibi doğal afetlerde durum, fikir, yardım istekleri ve bilgi paylaşılmasında önemli bir araçtır. Zengin bir veri kaynağı olan bu paylaşımlara dayalı deprem afet analizi çalışmaları olsa da deprem analiz yöntemlerinin etkinliğini doğrulamak için daha fazla vaka çalışması yapılmasına ihtiyaç vardır. Bu çalışmanın amacı deprem fırtınası sırasında X ağında paylaşılan tweetler üzerinden kamuoyunun gündemini, eğilimini ve davranışlarını belirlemek amacıyla tanımlayıcı analizler yapmaktır. Bu bağlamda python dili ve kütüphaneleri kullanılarak bir uygulama geliştirilmiştir. Bu uygulama ile ilk aşamada X ağında 5-12 Şubat 2023 tarih aralığında, içeriğinde “deprem” kelimesi geçen 2.643.481 adet tweet çekilerek bir veri seti oluşturulmuştur. Sonraki aşamada tanımlayıcı analizler yapılarak sonuçlar elde edilmiş ve bu sonuçlar veri görselleştirme araçları kullanılarak sunulmuştur. Elde edilen sonuçlar büyük bir afet sonrası kullanıcıların paylaşım davranışlarını ortaya koymuştur.
6 ŞUBAT 2023 TÜRKİYE’DEKİ DEPREM FIRTINASININ X (TWITTER) ÖZELİNDE TANIMLAYICI ANALİZLERİNİN YAPILMASI
Keywords: Graph; Social and Multimedia Data; Grafik; Sosyal ve Multimedya Verileri